Pengaruh Pendapatan Orang Tua terhadap Motivasi Belajar dan Hasil Belajar Siswa Pada Mata Pelajaran PAI di SMP Plus Attin Kota Kupang - Amin, Siti; Anton (Prodi Pendidikan Agama Islam, 2023)
This study aims to determine the effect of parental income on student learning motivation and student learning outcomes. The approach used in this research is quantitative approach with the type of correlation data analysis techniques used in data management are classical assumption which includes normality and linearity and final data T test. The research method used is simple linear regression. Based on test results using Microsoft Excel, it obtained the results of the research test of parental income 3.801T >Ttable, 3.803>1.703 and significance value 0.000<0.05. this means there is a positive and significant influence from parents' income to students' learning motivation. That means the better the income of parents the higher the motivation obtained. The results of the parental income test are 27.09 T>Ttabel, 27.09>1.703 and the significance value is 0.000<0.05. It means there is a positive and significant influence from parents' income to students' learning motivation.